THE APPLICATION OF COMPOST TO INCREASE PRODUCTION POTATO PLANTS (Solanum tuberosum L.) - Abraham Sanda Bannepadang; Tommy B. Ogie (Sam Ratulangi University, 2020)
The potato crop is a horticultural crop production during the times in a season. Indonesia has the production of potatoes is lower if compared with the State of Europe to the other. In developed countries such as the United States, New Zealand, Japan, and the Netherlands, the productivity of the potato range from 33 - 38 tons/ ha. While in Indonesia, the average production of only 15-16 tons/ha. In 2016, the potato plant has a productivity value of 1.2 million tons/ha with an average value of production that amounted to 16 tons/ha. The value is somewhat lower than the European production which has an average value of production of 25.5 tons/ha.Â Keywords: potato., compost., fertilizer.Â AbstrakTanaman kentang merupakan tanaman hortikultura yang berproduksi selama satu kali dalam semusim. Indonesia memiliki produksi kentang yang lebih rendah jika dibandingkan dengan Negara bagian Eropa yang lain. Di Negara maju seperti Amerika Serikat, Selandia Baru, Jepang, dan Belanda produktivitas kentangnya berkisar 33- 38 ton/ ha. Produksi di Indonesia rata-rata hanya 15-16 ton/ha. Pada tahun 2016, tanaman kentang memiliki nilai produktivitas sebesar 1,2 juta ton/ha dengan nilai rata-rata produksi sebesar 16 ton/ha. Nilai tersebut terbilang rendah dari nilai produksi Eropa yang memiliki nilai rata-rata produksi sebesar 25,5 ton/ha.Â Kata kunci : kentang., kompos., pupuk.